An Optimal Cost Estimation Practices of Fuzzy AHP for Building Construction Projects in Libya - Walid Alfaggi; Sepanta Naimi (Civil Engineering Journal, 2022)
This paper analysis and reviews the construction projects in Libya. In Libya, construction projects often face challenges due to the lack of proper information and data in cost-estimation methods. The primary goal of this paper is to demonstrate the estimation of construction costs using various methods. An optimization strategy based on a well-known robust algorithm The Fuzzy AHP technique is used to estimate the best roof structure choice based on cost rank among one or two-way flat slab, post-tension slab, pre-tension slab, waffle slab, and hollow core slab. The roofs were created employing five main factors that were implemented in a real-world situation in the Libyan building industry. The cost of materials, labor, machinery, transportation, and trash on site were all considered. Research findings show that the models can assist decision-makers in determining the cost rank of roof selection. When a range of methods are applied and compared to guarantee that this is the best option. This research study must be taken seriously when estimating and managing the contract and length of highway construction projects in the early stages of project development so that the time difference at the end of the project can be kept to a minimum by decision-makers when choosing the roof with the lowest cost. Doi: 10.28991/CEJ-2022-08-06-08 Full Text: PDF